2003
DOI: 10.1063/1.1587695
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Li ions in an intercalated polymer electrolyte: A 7Li nuclear magnetic resonance study

Abstract: The 7 Li nuclear magnetic resonance spectra and spin-lattice relaxation rates of lithium ions in an intercalated polymer electrolyte, Li-polyethylene-oxide confined within the galleries of an inorganic layered solid CdPS 3 , are reported. The spectra show an unusual feature, the appearance above 330 K of quadrupolar satellites, whose splitting increases linearly with temperature, and their absence below this temperature. This behavior is also reflected in the temperature variation of the spin-lattice relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…37 Indeed, an Einstein oscillator model for such a motion predicts a linear increase in the quadrupolar coupling with temperature 35,37 ͓a more detailed analysis of the origin and temperature dependence of the quadrupolar coupling in Cd 0.75 PS 3 Li 0.5 (PEO) is presented in the following paper͔. 38 The linewidth ͑FWHM͒ of the central (1/2↔Ϫ1/2) transition of the experimental 7 Li spectra of Cd 0.75 PS 3 Li 0.5 (PEO) has been plotted as a function of temperature in Fig. 6.…”
Section: B 7 LI Nmr and Motion Of Li Ionsmentioning
confidence: 97%
“…37 Indeed, an Einstein oscillator model for such a motion predicts a linear increase in the quadrupolar coupling with temperature 35,37 ͓a more detailed analysis of the origin and temperature dependence of the quadrupolar coupling in Cd 0.75 PS 3 Li 0.5 (PEO) is presented in the following paper͔. 38 The linewidth ͑FWHM͒ of the central (1/2↔Ϫ1/2) transition of the experimental 7 Li spectra of Cd 0.75 PS 3 Li 0.5 (PEO) has been plotted as a function of temperature in Fig. 6.…”
Section: B 7 LI Nmr and Motion Of Li Ionsmentioning
confidence: 97%
“…Although unexpected, in the literature similar coupling constant increase effects have already been described for other systems: Ludwig et al had found a linear increase of the deuteron quadrupole coupling constant of water in a water and dimethyl sulfoxide mixture of 0.08 kHz K À1 in the temperature range from 188 K to 308 K. 33 In liquid ammonia a linear temperature dependence of 0.1 kHz K À1 was determined by Hardy et al for the deuteron quadrupole coupling constant in the temperature range from 237 K up to 293 K. 34 A linear temperature dependence of the 7 Li quadrupolar coupling constant of 0.05 kHz K À1 above 330 K was found by Arun et al in an intercalated polymer electrolyte (IPE), Cd 0.75 PS 3 Li 0.5 (PEO). 35 Further examples of the increase of the quadrupole coupling constant in liquids can be found elsewhere. 36,37 The increase of the quadrupole coupling constant with temperature can be explained by different mechanisms.…”
Section: Model Including a Temperature Dependent Prefactormentioning
confidence: 99%
“…On the other hand, Arun et al explained the temperaturedependence of A by changes in the time average of the EFG using an anisotropic quantum oscillator model. 35 Other possible explanations are a change of the EFG induced by a change of the atomic coordinates or induced by a change of the electron density distribution. 39 In our system, a change of the electron density distribution might occur, induced by a change of the coordination structure of the lithium ion.…”
Section: Model Including a Temperature Dependent Prefactormentioning
confidence: 99%